Reaching for health The Australian women's health movement and public policy - Gray Jamieson, Gwendolyn (ANU Press, 2012)
The women's health movement shocked and scandalised when it burst into Australian politics in the early 1970s. It cast the light of day onto taboo subjects such as sexual assault, abortion and domestic violence, provoking outrage and condemnation. Some of the services women created for themselves were subjected to police raids; sex education material was branded 'indecent'. Moreover, women dared to criticise revered institutions, such as the medical system. Yet for all its perceived radicalism, the movement was part of a much broader and relatively conventional international health reform push, which included the 'new' public health movement, the community health centre movement and, in Australia, the Aboriginal health movement, all of which were critical of the way medical systems had been organised during the 20th century. The women who joined the movement came from diverse backgrounds and included immigrant and refugee women, Aboriginal women and Anglo women. Initially, groups worked separately for the most part but as time went on, they found ways to cooperate and collaborate. This book presents an account of the ideas, the diverse and shared efforts and the enduring hard work of women's health activists, drawn together in one volume for the first time. This relentless activism gradually had an impact on public policy and slowly brought forth major attitudinal changes. The book also identifies the opportunities for health reform that were created along the way, opportunities which deserve to be more fully embraced.